Calcification of hydrophilic acrylic intraocular lenses associated with intracameral air injection following DMEK. Issue 6 (June 2015) - MacLean, Kyle D.; Apel, Andrew; Wilson, Jessica; Werner, Liliana
Abstract : N/A: We present 2 cases of localized calcification on the anterior surface/subsurface of hydrophilic acrylic intraocular lenses (IOLs) following procedures involving intracameral injection of air. Although this phenomenon has been reported in hydrophilic acrylic IOLs, to our knowledge it has not been reported in the IOLs described in our cases, one a sulcus‐fixated supplementary IOL and the other a hydrophilic acrylic IOL with a hydrophobic surface. Centralized opacity of the IOLs was first noted months after Descemet membrane endothelial keratoplasty had been performed in both cases; explantation was required. Laboratory analysis of the IOLs confirmed calcification of the anterior surfaces in a localized pattern in the area of the capsulorhexis or pupil. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.